Enhancing Job Performance Through Work Engagement: The Role of Perceived Organizational Support Among Non-Medical Employees - Padilah Hamzah; Agi Syarif Hidayat (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
This study aims to analyze the effect of Perceived Organizational Support (POS) on Job Performance, with Work Engagement as a mediating variable among non-medical employees at RSUD Waled, Cirebon (n = 102). The research employed a quantitative approach using a survey method. Data were collected through questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that POS has a positive and significant effect on Work Engagement (β = 0.540; t = 6.407; p < 0.001). Work Engagement also has a positive and significant effect on Job Performance (β = 0.533; t = 6.237; p < 0.001), while the direct effect of POS on Job Performance is not significant (β = 0.015; t = 0.150; p = 0.881). In addition, the indirect effect of POS on Job Performance through Work Engagement is significant (β = 0.288; t = 3.939; p < 0.001), indicating that Work Engagement functions as a mediating variable in this relationship. These findings suggest that organizational support is more effectively translated into Job Performance through the enhancement of Work Engagement, highlighting the important role of Work Engagement in explaining the relationship between organizational support and the performance of non-medical employees.